MODERASI DAN TOLERANSI: MEMBANGUN PENDIDIKAN MULTIKULTURAL YANG HARMONIS - Ridwana Siregar; Zainal Efendi Hasibuan (Yayasan Baitul Hikmah al-Zain, 2024)
Moderate multicultural education plays a crucial role in fostering harmony and tolerance within diverse communities of various cultures and religions. This approach emphasizes the importance of respecting and understanding differences as sources of richness rather than conflict. Anchored in Islam, moderate multicultural education aims to create an inclusive learning environment and facilitate intercultural dialogue. By leveraging both formal and informal education, and employing openness, inclusive content, and dialogic teaching methods, moderate multicultural education seeks to cultivate peaceful, tolerant attitudes and behaviors that honor diversity in everyday life. Multicultural education is a crucial approach in addressing the complexities of today's global society. By recognizing and appreciating cultural diversity, this education aims not only to foster cross-cultural understanding but also to develop critical thinking skills, empathy, and intercultural cooperation. Effective implementation of multicultural education requires strong commitment from educational institutions to integrate universal values of human rights, social justice, and global peace into daily curricula and teaching practices. Therefore, multicultural education not only prepares future generations to tackle global challenges but also promotes social harmony and inclusion in an increasingly interconnected and complex world. Therefore, the implementation of moderate multicultural education is expected to strengthen interfaith harmony and cohesion in Indonesia.